Viability of Vanda limbata Orchid Seeds With Diferent Storage Period in Organic Tomato Extract Media - Ni Putu Yuni Astriani Dewi; Yunawati Sele; Theresia Oriyanti Luruk (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Orchid propagation using seeds is very difficult to develop conventionally, because orchid seeds do not have endosperm. Research regarding the shelf life of orchid seeds is important as an effort to determine the viability/ability of orchid seeds to germinate. Propagation through tissue culture techniques with shelf life of seeds is one of the conservation and multiplication efforts of horticultural plants. This research aims to determine the germination ability of Vanda limbata orchid seeds stored for different periods of time through the development phases of Vanda limbata orchid embryos. Methodology: This research used a Completely Randomized Design with three treatments, namely fresh orchid seeds, orchid seeds stored for 1 week and orchid seeds stored for 3 weeks with each treatment having 5 replications. This research using organic tomato extract media as a natural growth regulator. Findings: The results of the research showed that V. limbata orchids planted fresh (P1) experienced growth and development until they reached phase 6 (Short Apical Meristem (SAM) was detected and were green), and during the 1 week storage period they reached phase 5 growth and development (the size of the embryo was round, enlarged and green), whereas seeds stored for 3 weeks only experienced growth and development reaching phase 3 (the embryo was round or oval, the testa was still white and had no testa). the three treatments orchid seeds that were planted directly without the seed storage process experienced faster seed germination than seeds that were stored for 1 or 3 weeks.  Contribution:  This research has an important contribution to ex situ orchid conservation